Effects of the continuous subcutaneous infusion of foslevodopa-foscarbidopa on swallowing in patients with Parkinson’s disease - Makito Hirano; Makoto Samukawa; Chiharu Isono; Rino Inada; Yuta Fukumoto; Keisuke Yoshikawa; Hitoshi Namura; Hanami Sakata; Takahiro Hisatomi; Toru Michiura; Hiroto Nakamura; Akira Morita; et al. (Clinical Parkinsonism & Related Disorders)
Background: Dysphagia is a potentially fatal symptom of Parkinson’s disease (PD) and is characterized by frequent silent aspiration, a known risk factor for aspiration pneumonia. A previous study has reported that the dopamine agonist rotigotine (levodopa equivalent dose of 60 mg/day) delivered via transdermal patch improves swallowing function more effectively than oral levodopa (200 mg/day), highlighting the importance of continuous dopaminergic stimulation (CDS) in managing dysphagia. To achieve CDS, patients with advanced PD may require device-assisted therapies (DATs), including levodopa–carbidopa intestinal gel (LCIG), which have significantly improved swallowing function on some measures. In contrast, swallowing function is an important prognostic factor for patients with PD undergoing LCIG. Continuous subcutaneous infusion of foslevodopa/foscarbidopa (CSCI-FF) is a newly developed DAT; however, its effect on swallowing function remains unknown. Methods: This retrospective open-label evaluator-blinded study included seven patients with PD. Swallowing function was assessed using videofluoroscopic swallow studies (VFSS) conducted before and after initiating CSCI-FF. Evaluations included the Japanese Swallowing Scale, the Dysphagia Outcome and Severity Scale (DOSS), Penetration/Aspiration Scale, oral transit time (OTT), and pharyngeal transit time (PTT). Results: Following the introduction of CSCI-FF, results of VFSS showed significant improvement in the total score of the Japanese swallowing scale, OTT, and PTT. Conclusions: This study provides preliminary evidence that CSCI-FF may partially improve swallowing function in patients with advanced PD. Further research with larger cohorts is warranted.